EFEKTIVITAS KOMBINASI EKSTRAK BAHAN HERBAL (Mengkudu, Pepaya, Kunyit) TERHADAP DAYA HAMBAT PERTUMBUHAN Aeromonas hydrophila SECARA IN VITRO - Dadi Pratama; Agung Budiharjo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
. One of the alternative to overcome bacterial diseases of fish is by using herbal material that contain antibacterial. This study aimed to test the effectiveness of a combination of herbal material extract (noni, papaya and turmeric) in controlling the growth of bacteria Aeromonas hydrophila in-vitro. The research design used was Completely Randomized Design (CRD), which consists of 33 treatments and 3 replications. The parameters measured were the absorbance value (λ = 600 nm) of A. hydrophila growth after 18 hours of incubation and was measured by multiskan GO microplate spectrophotometer. This research was conducted through a two-stage test, the test MIC and FIC using microdilution method. MIC test result showed the minimum dosage of each herbal extract that is 1 µl/ml for noni extract, 2 µl/ml for papaya extract, and 1 µl/ml for turmeric extract. Values obtained FIC index is 0.250 (combination MP), and 0.375 (a combination of MK and PK). The combination of herbal material each extract showed synergistic interaction with FIC index values ≤ 0.5. Formula of the most effective and efficient than any combination is 1/8x noni and 1/4x papaya, 1/4x noni and 1/8x turmeric, 1/4x papaya and 1/8x turmeric. Keywords: Antibacterial, A.hydrophila, FIC Indeks